Upaya Deteksi Dini Risiko Tinggi Kehamilan Ditentukan Oleh Pengetahuan Dan Pemeriksaan Kehamilan Di Pulau Osi - Arindiah Puspo Windari; Sri Ayu Lohy (Poltekkes Kemenkes Denpasar, 2019)
The most common cause of maternal death is bleeding (30.3%), followed by hypertension in pregnancy (27.1%), infection (7%). Other causes, 45%, are quite large, including non-obstetric causes. High maternal mortality is also caused by the high number of unexpected pregnancies. Approximately 65% of pregnancies still occur because